Comportamento de indicadores de saúde de trabalhadores rurais após ações de educação em saúde - Glänzel, Marcelo Henrique; Nepomuceno, Patrik; Couto, Analie Nunes; Santos, Carine Muniz dos; Severgnini, Cassiano; Santos, Polliana Radtke dos; Kleinpaul, William Vinicius; Reckziegel, Miriam Beatrís; Pohl, Hildegard Hedwig (Saúde (Santa Maria), 2022)
INTRODUCTION: In Brazil, 16 of 90 million workers perform their work activities in rural areas, which is the country’s economy closely associated with rural production. However, health care provided to rural areas is less than that offered to the urban population. The diseases that affect these populations are similar, but, there is higher mortality in the rural environment. PURPOSE: This study aimed to identify the behavior of the metabolic, morphologic, and physical fitness parameters of rural workers after health education. METHODS: Metabolic, morphologic, and physical fitness parameters of seventeen rural workers were assessed. After health education, the subjects returned to the laboratory three years later and repeated the assessments. RESULTS: Reductions in metabolic variables: total cholesterol (-8.0%; p = 0.031), LDL-c (-19.1%; p = 0.005), and triglycerides (-19.1%; p = 0.044); while increases in HDL-c (18.1%; p = 0.001), resting heart rate (9.5%; p = 0.046), and body fat (14.5%; p = 0.001) also has been founded. FINAL CONSIDERATIONS: Health education promotes positive changes in the lipid profile, but not in the morphologic and physical fitness parameters of the rural workers. It is suggested that less frequent education actions can minimize health risks, contributing to improving the health of rural workers.